The return of depression economics and the crisis of 2008 [compact disc, unabridged] - Krugman, Paul R. (Random House Audio, 2009)
Paul Krugman reveals the striking similarities between the 2008 economic crisis and the Great Depression. Filled with Krugman's cynic wit, listeners will be shocked as they discover the gaffs and blunders that caused the most recent economic blues.